2020
DOI: 10.1371/journal.pone.0232465
|View full text |Cite|
|
Sign up to set email alerts
|

Reliability of technologies to measure the barbell velocity: Implications for monitoring resistance training

Abstract: This study investigated the inter-and intra-device agreement of four new devices marketed for barbell velocity measurement. Mean, mean propulsive and peak velocity outcomes were obtained for bench press and full squat exercises along the whole load-velocity spectrum (from light to heavy loads). Measurements were simultaneously registered by two linear velocity transducers T-Force, two linear position transducers Speed4Lifts, two smartphone video-based systems My Lift, and one 3D motion analysis system STT. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 37 publications
3
67
0
3
Order By: Relevance
“…In stating this, future research must consider utilising a broader range of exercises (e.g., Olympic weightlifting exercises and their derivatives) and loads to be confident of the reliability and validity of devices. For the assessment of reliability, only three studies have assessed the agreement between two different devices of the same brand (i.e., inter-device) [22,36,51]. In contrast, there has been a substantial amount of research concerning intra-device reliability [28,48,52]; however, it must be noted that all but one of these studies [22] failed to differentiate technological variation from biological variation to establish their respective influence on the unit's reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stating this, future research must consider utilising a broader range of exercises (e.g., Olympic weightlifting exercises and their derivatives) and loads to be confident of the reliability and validity of devices. For the assessment of reliability, only three studies have assessed the agreement between two different devices of the same brand (i.e., inter-device) [22,36,51]. In contrast, there has been a substantial amount of research concerning intra-device reliability [28,48,52]; however, it must be noted that all but one of these studies [22] failed to differentiate technological variation from biological variation to establish their respective influence on the unit's reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with the increasing interest in monitoring resistance training performance, mobile phone apps have also become available [10,24,36,69,70]. While there is conflicting evidence [24,36,51,70], it appears that substantial bias and error can be introduced when different devices and/or users implement these measuring tools [23]. Thus, practitioners should ensure thorough familiarisation and standardised protocols when using these applications.…”
Section: Validitymentioning
confidence: 99%
“…Characteristics of the included studies can be found in Table 3 . The apps presented in the included articles were compared with motion a capture system [ 40 , 61 , 68 , 69 ], linear encoder and transducers [ 56 , 59 , 60 , 62 , 63 , 64 , 71 ], as well as with contact platforms [ 37 , 39 , 41 , 57 , 61 , 62 , 63 , 66 ], accelerometers [ 59 , 62 , 63 , 68 , 70 ], and time photocells [ 55 , 65 , 67 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, [ 39 , 53 , 56 , 59 , 62 , 63 , 64 ] tested the bench press, [ 64 , 68 ] the back squat, [ 60 ] the half squat and full squat [ 39 , 53 ], [ 40 ] the snatch, [ 53 ] the hip thrust, [ 68 ] the power clean, [ 37 , 41 , 57 , 61 , 66 , 71 ] the vertical jump (CMJ, SJ or DJ), [ 58 ] the running, [ 65 , 67 ] the sprint or agility [ 55 , 70 ] the static and dynamic arm swing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation